DuPont Analysis of Luxury Industry and Market Portfolio : A Comparative Study - Bothra, Neha; Gupta, Saloni (Indian Journal of Finance, 2020)
The measurement of financial performance is primarily based on return on equity (ROE) ratio. The DuPont model analyzes the sources of financial performance (ROE) of a firm. The luxury industry tends to drive high profitability in the market vis-a-vis the market counterparts. Is this an enough evidence to believe that the ROE is majorly contributed by profitability of the luxury firms ? The study intended to test the impact of firms’ profitability, asset efficiency, and financial leverage on ROE in the luxury industry (LI) and the non-luxury industry (NLI). The paper conducted the DuPont analysis, and a comparison between luxury industry and non-luxury industry was drawn. The empirical findings claimed that the maximum beta-coefficient was contributed by efficiency of a firm, which was measured by ATR for dependent variable ROE. On establishing a comparison, the results were found to be similar even in the luxury industry.